2018
DOI: 10.21512/humaniora.v9i3.4937
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Javanese Society: A Study in Language Forms Choice to Men and Women

Abstract: This research aimed to reveal different ways of thinking of society for men’s and women’s positions from the sociolinguistic point of view to accomplish the previous research. The research was conducted by studying language data in sentence formation on short story (fiction) and article (nonfiction). The short story and article used as data sources originated from internet media. This research used a qualitative descriptive method. The data were analyzed using equality and distributional methods. The finding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…In the context of INAP-L, the potential for item bias can occur due to gender differences. This opinion is in line with the findings of previous studies which state that language tests tend to be gender biased (Atmawati, 2018). In addition, other study have found that there is a significant difference between the language skills of men and women in the Indonesian sample (Almuzakir & Qamariah, 2019).…”
Section: Introductionsupporting
confidence: 90%
“…In the context of INAP-L, the potential for item bias can occur due to gender differences. This opinion is in line with the findings of previous studies which state that language tests tend to be gender biased (Atmawati, 2018). In addition, other study have found that there is a significant difference between the language skills of men and women in the Indonesian sample (Almuzakir & Qamariah, 2019).…”
Section: Introductionsupporting
confidence: 90%
“…Besides, education is a tool not only to get proper jobs but also to change one's mindset in social life. This is in line with the research of Atmawati (2018) that has said the way of social thinking is determined by the differences of language choice, in which it develops in accordance with the education level pursued. If women do not get an education, it will not only make it difficult for them to find jobs and to improve their living standard but also inhibit their social life because they are considered not able to put themselves on the same level as educated men.…”
Section: Introductionsupporting
confidence: 88%
“…Shalaby (2019) stated that most people are exposed to hundreds of advertisements that encourage them to purchase certain products on a daily basis which seen as "socializing agents" that construct people"s ideologies and standards. Atmawati (2018) discussed that Language forms choice of someone can be different from language formation choice of others when speaking. Those differences come from sex difference and local culture as well.…”
Section: Review Of Literaturesmentioning
confidence: 99%